2020
DOI: 10.3892/etm.2020.9022
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‑catenin signaling may induce senescence of chondrocytes in osteoarthritis

Abstract: Osteoarthritis (OA) is an autoimmune disease associated with increasing age. Typically, chondrocyte senescence is believed to serve an important role in the development and progression of OA. However, the specific mechanisms underlying chondrocyte senescence have not been fully addressed. The present study hypothesized that the Wnt/β-catenin signaling may represent a major regulator of chondrocyte senescence. In addition, the acetylated levels of p53 and sirtuin-1 (SIRT-1) were examined as putative markers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Our experimental data also corroborated that SIRT1 restoration also relieved metabolic imbalance, extracellular matrix degradation and augmented chondrocyte autophagy in OA-like mice or microenvironment. Consistent evidences have reported that SIRT1 overexpression led to decreased apoptotic rates of chondrocytes [ 20 ], and SIRT1 knockdown may result in chondrocyte senescence [ 21 ]. It has been found that improved extracellular matrix degradation of IL-1β-induced chondrocytes can be led by downregulated MMP-13 and ADAMTS-5 [ 22 ].…”
Section: Discussionsupporting
confidence: 53%
“…Our experimental data also corroborated that SIRT1 restoration also relieved metabolic imbalance, extracellular matrix degradation and augmented chondrocyte autophagy in OA-like mice or microenvironment. Consistent evidences have reported that SIRT1 overexpression led to decreased apoptotic rates of chondrocytes [ 20 ], and SIRT1 knockdown may result in chondrocyte senescence [ 21 ]. It has been found that improved extracellular matrix degradation of IL-1β-induced chondrocytes can be led by downregulated MMP-13 and ADAMTS-5 [ 22 ].…”
Section: Discussionsupporting
confidence: 53%
“…It was also found that Sox9 overexpression could inhibit the level of β-catenin during cartilage repair in vivo [26] . Therefore, the mutual inhibition between Sox9 expression and classical Wnt/β-catenin signaling pathway indicates that chondrocyte differentiation may be regulated by a positive feedback loop mechanism: inhibition of classical Wnt signaling pathway causes Sox9 expression; Sox9 further inhibited Wnt/β-catenin signal and osteogenic differentiation, thus promoting the complete differentiation of chondrocytes [27] .…”
Section: Resultsmentioning
confidence: 99%
“…Human β-catenin protein is an 88-kDa cytoskeletal protein, 781-amino acid long, encoded by the catenin beta-1 gene (CTNNBI) and located on the 3p21 human chromosome ( 21 ). Numerous studies have shown that β-catenin is a major signaling molecule in the Wnt signaling pathway ( 22 - 24 ). Wnt signaling pathway activation depends on β-catenin expression levels in the cell ( Fig.…”
Section: Discussionmentioning
confidence: 99%